CD83 expression is essential for Treg cell differentiation and stability - Döbbeler, Marina; Koenig, Christina; Krzyzak, Lena; Seitz, Christine; Wild, Andreas; Ulas, Thomas; Bassler, Kevin; Kopelyanskiy, Dmitry; Butterhof, Alina; Kuhnt, Christine; Kreiser, Simon; Stich, Lena; et al. (JCI Insight, 2018)
Foxp3-positive regulatory T cells (Tregs) are crucial for the maintenance of immune homeostasis and keep immune responses in check. Upon activation, Tregs are transferred into an effector state expressing transcripts essential for their suppressive activity, migration, and survival. However, it is not completely understood how different intrinsic and environmental factors control differentiation. Here, we present for the first time to our knowledge data suggesting that Treg-intrinsic expression of CD83 is essential for Treg differentiation upon activation. Interestingly, mice with Treg-intrinsic CD83 deficiency are characterized by a proinflammatory phenotype. Furthermore, the loss of CD83 expression by Tregs leads to the downregulation of Treg-specific differentiation markers and the induction of an inflammatory profile. In addition, Treg-specific conditional knockout mice showed aggravated autoimmunity and an impaired resolution of inflammation. Altogether, our results show that CD83 expression in Tregs is an essential factor for the development and function of effector Tregs upon activation. Since Tregs play a crucial role in the maintenance of immune tolerance and thus prevention of autoimmune disorders, our findings are also clinically relevant.
EVALuna2:36212